Can a Nonspecific Bias Toward Top-Heavy Patterns Explain Newborns' Face Preference? - Viola Macchi, Cassia; Turati, Chiara; Simion, Francesca (Psychological Science, 2004)
This study examined newborns' face preference using images of natural and scrambled faces in which the location of the inner features was distorted. The results demonstrate that newborns' face preference is not confined to schematic configurations, but can be obtained also with veridical faces. Moreover, this phenomenon is not produced by a specific bias toward the face geometry, but derives from a domain-general bias toward configurations with more elements in the upper than in the lower half (i.e., top-heavy patterns). These results suggest that it may be unnecessary to assume the existence of a prewired tendency to orient toward the face geometry, and support the idea that faces do not possess a special status in newborns' visual world.